Quality of life and conditioning factors in people with Non-syndromic Cleft Lip and Palate (NSCLP): experiences of family members, patients, and health personnel - Jaramillo-Rojas, Ana María (2024)
Objective: Understand the perceptions and experiences about quality of life (QOL) and their conditionants in people with Non-syndromic Cleft Lip and Palate (NSCLP), from the experience of people living with this condition, and from their families and health personnel. Methods: A qualitative study with phenomenological perspective was conducted. Six individuals and relatives (partner, siblings, parents) were interviewed. This information was complemented by an interview with an orthodontist who works with people with NSCLP and a Focus Group with the participation of health personnel working in a Specialized Foundation focused on these individuals. Qualitative content analysis and phenomenological reduction strategies were carried out to address the main themes extracted from the discourses of the participating population. Ethical and institutional approval was obtained. Results: Four main categories of the experience of people with NSCLP were found that involve the different perspectives of the study participants: 1) concept of QOL and its conditioning factors, 2) life experience with the condition of NSCLP; 3) experience during comprehensive treatment for NSCLP condition; and 4) general expectations. All these categories reflect the life history, the individual and social elements, and the difficulties inherent to their condition. Conclusions: there are individual, social, and contextual factors that affect the QOL of people living with NSCLP. This situation implies an intersectoral and multidisciplinary approach that allows the generation of health policies and treatment strategies according to the individual and collective people’s needs.